DIGITAL FATIGUE: A CASE STUDY OF CULINARY ARTS STUDENTS ON THE ONLINE DISTANCE LEARNING (ODL) DURING PANDEMIC-19 - Norfezah Md Nor; Nur Sabrina Abdul Razak; Mohd Syafiq Othman (Journal of Islamic, Social, Economics and Development, 2022)
The pandemic shifted universities teaching and learning from in-person to online distance learning (ODL) in an instant, including the Culinary Arts students, Universiti Teknologi MARA Cawangan Pulau Pinang they were not exempted from this adjustment. This abrupt transition has disrupted their learning process and triggered a plethora of concerns, which is a digital fatigue. Therefore, this study aimed to identify causes towards the digital fatigue faced by culinary students in UiTM Cawangan Pulau Pinang during ODL classes. A qualitative research approach was employed with a total of eleven (11) students were interviewed using a semi-structured interview questions. The findings revealed that there were nine (9) factors contributed towards digital fatigue with five main factors influenced the most; technology issue, academic overload, screen time, sedentary behaviour and time management. Early identification causes of digital fatigue may help to mitigate the issues.